Seawater to resource technologies with NASICON solid electrolyte: a review - Kim, Namhyeok; Kim, Seohae; Jeong, Seongwoo; Jin, Hyo; Lee, Hyeonseok; Kim, Youngsik; Lee, Wang-Geun; Park, Jeong-Sun (Frontiers in Batteries and Electrochemistry, 2023)
Seawater represents an inexhaustible reservoir of valuable resources, containing vast quantities of both water and minerals. However, the presence of various impurities in seawater hinders its direct utilization for resource extraction. To address this challenge, an electrochemical method employing a solid electrolyte known as NASICON (Sodium Super Ionic Conductor) offers effective solutions for extracting valuable resources from seawater. The NASICON ceramic acts as a robust barrier against impurities and facilitates the selective transport of Na + . This review provides a comprehensive examination of NASICON ceramics, offering an overview of the concept and highlighting the competitive advantages of NASICON-based electrochemical systems, particularly in the realms of energy storage, hydrogen production, sodium hydroxide and chlorine synthesis, water treatment, and mineral extraction. Furthermore, this study outlines the key challenges that need to be addressed and discusses the trajectory of its development toward becoming a mature technology.